Implementation of School Literacy Movement in Improving Students' Reading Interests at SMPN 14 Mataram - Hardiansyah, Hardiansyah; Sigap, Sigap; Murtadlo, Murtadlo; Wulandari, Ayu (UNDIKMA, 2025)
The objectives of this study are: 1) To find out about how the implementation of the school literacy movement in increasing reading interest is implemented at SMP Negeri 14 Mataram; 2) To find out the literacy programs that have been developed to increase students' interest in reading; 3) To provide an overview of the inhibiting and supporting factors in implementing the school literacy movement in increasing students' interest in reading. Data collection techniques include observation, interview, and documentation. Data analysis is used for data reduction, data presentation, and conclusion. The results of the study showed that SMPN 14 Mataram had implemented the GLS program by instilling reading habits, and the principal made a School Literacy Team Decree, the GLS program used was Habituation, self-development, and insertion in learning. The implementation of GLS has a positive impact on the school community and the implementation of the literacy movement is still in the development stage. Developing Programs: 1) Reading and writing in the form of activities 15 minutes of reading; 2) Numeracy; 3) Science; 4) Digital; 5) Financial; 6) Culture and Citizenship; 7) Literacy festival. The supporting factors for the GLS program are the support of the principal and teachers the issuance of the School Literacy Team Decree, the availability of books, and GLS programs. Factors inhibiting GLS include students' lack of awareness and interest in reading, teachers are often late to class so that no one supervises students' literacy activities, limited books, and inadequate library buildings.